The effects of logic replacement in coal-mining disaster: the case of Soma - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2016)
Purpose - Drawing from the institutional logics and organizational disaster literature, this paper aims to illustrate that the replacement of logics can be problematic in a high-risk industry such as coal mining by adding an institutional perspective to the understanding of disasters. Design/methodology/approach - This paper investigated the field of coal mining in Turkey historically from archival data resources. A comprehensive, qualitative inquiry of a single-case study was then conducted. Findings - The findings suggest that a shift from social welfare logic to business logic in the coal-mining industry can lead to coal-mining disasters, resulting from changing practices through an increase in the number of private enterprises through royalty contracts, the use of an increased labor force instead of mechanical methods and systems and the maximization of profit by underestimating the effects of taking almost no occupational safety measures. Practical implications - The connection between institutional logics and organizational disasters could lead institutional actors to question their understanding of institutional logics. Originality/value - This paper provides original research evidence for the relationship between industrial disasters and institutional logics.
Keywords: Institutional logics; Industrial disaster; Logic shift; Man-made disaster; INSTITUTIONAL LOGICS; ORGANIZATIONS; RESPONSES